Breaking Barriers: Insights into Leadership Dynamics and Challenges of Women in Business from Kashmir Valley, India - Omar F. Khan; Arijmand Shahid (Journal of Women Entrepreneurship & Business Management (e-ISSN: 2583-8210), 2024)
In business, women’s entrepreneurship is a vibrant and dynamic force in the 21st century. The research presented in this paper explores women’s entrepreneurship in the Kashmir Valley from various dimensions, including success metrics, obstacles faced, and motivational factors. The study garnered responses from 40 women entrepreneurs, showcasing a diverse business landscape, with packaging being the most dominant sector. The main drivers for women entrepreneurs were financial gain and profit potential, social impact, personal fulfilment, and independence. Access to funding emerged as the most prevalent challenge, highlighting the critical importance of financial resources for entrepreneurial success. Risk-taking, uncertainty, and gender bias were significant hurdles that women entrepreneurs encountered, underscoring the need for focused support systems and laws to address these issues. Strategies such as mentorship, robust support systems, and alternate funding sources are essential for overcoming these obstacles and fostering entrepreneurial success. Moreover, the research study identified key success dimensions for women entrepreneurs, with personal happiness emerging as the most significant determinant of entrepreneurial success. Achieving one’s objectives, maintaining financial security, and gaining respect in the workplace are all necessary measures of success that highlight the complexity of entrepreneurial pursuits. Strategies like customer focus, effective marketing, and innovation are essential to drive corporate growth and sustainability. This emphasizes the significance of adaptation and creativity in the entrepreneurial process. Policymakers, stakeholders, and support entities can foster an environment that empowers women to thrive in entrepreneurship and thereby contribute to greater gender diversity and financial independence in the Kashmir Valley by recognizing and tackling the particular challenges and opportunities faced by women entrepreneurs in the region.